Becoming smart “digital natives”: cultivating Chinese English majors’ new media literacy via Journalism English Reading and Listening - Zhang Danyang; Wu Yang (Journal of China Computer-Assisted Language Learning)
In the current era, digital technologies, including multimedia and communication technologies, have penetrated almost every aspect of our lives. English majors are responsible for learning English languages and western cultures and serve as interlocutors between the East and the West. Therefore, such students need to be new media literate to retrieve, understand and evaluate information from multimedia sources and actively and critically participate in the digital environment. Nevertheless, very few studies have explored this group of students’ new media literacy (NML) level or their NML development via instructed training. This mixed methods study explores a group of Chinese English majors’ current NML level. It attempts to cultivate their NML via a course named Journalism English Reading and Listening. In total, by applying purposive sampling, 70 Chinese English majors were invited to participate in the study. The participants completed a pre- and post-course questionnaire based on Lin et al.’s (2013). Understanding new media literacy: An explorative theoretical framework. Journal of Educational Technology & Society, 16(4), 160–170) NML framework to quantitatively self-evaluate their NML. Results demonstrate that the participants’ consuming media literacy significantly improved. Regarding the participants’ prosuming media literacy, three constructs, including prosuming skill, production, and creation, exhibited significant improvements, but no significant differences were found in distribution and participation. This paper also introduces examples of the students’ group work to qualitatively showcase their NML development. Finally, the study offers insights into Chinese English majors’ professional training and development.